Photo- and thermo-oxidative aging of polypropylene filled with surface modified fumed nanosilica. (March 2017) - Lu, Ming; Gao, Xiaowei; Liu, Peng; Tang, Hanying; Wang, Feng; Ding, Yanfen; Zhang, Shimin; Yang, Mingshu
Abstract: Fumed nanosilica (FS) was treated separately by different silane coupling agents, including n -dodecyl-trimethoxyl silane (DTMS), aminoethylaminopropyl-trimethoxyl silane (AEAPS), aminopropyl-trimethoxyl silane (APS) and methacryloxypropyl-trimethoxyl silane (MAPS). Their influences on photo- and thermo-oxidative aging of polypropylene were evaluated by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and thermal gravimetric analysis (TGA). The photoaging of polypropylene was accelerated by the MAPS-modified FS but delayed by the neat FS and other modified FS. On the other hand, the thermal and thermo-oxidative stability of polypropylene were improved with the incorporation of the nanoparticles, independent of the modification. The AEAPS-modified FS and the APS-modified FS revealed simultaneously noticeable enhancement in both photo-stability and thermo-oxidative stability of polypropylene. The possible mechanism was discussed. Highlights: The DTMS-modified FS accelerated the photo-degradation of polypropylene (PP). The AEAPS-modified FS could induce the formation of β-PP which is more stable than α-PP toward photo-degradation. The AEAPS-modified FS and APS-modified FS improved both the photo-stability and thermo-oxidative stability of PP significantly.